Effects of Media Literacy Intervention on Weight-Control Products Digital Marketing Targeting Adolescents - Li-Chuan Lin; Fong-Ching Chang; Tzu-Fu Huang; Tai-Yu Chen; Chiung-Hui Chiu; Ping-Hung Chen; Nae-Fang Miao; Hung-Yi Chuang; Hsueh-Chih Chen (Behavioral Sciences)
This study aimed to evaluate the effects of a media literacy education intervention on adolescents’ responses to digital marketing of weight-control products, focusing on media literacy, persuasion resistance efficacy, and purchase intention. Using a quasi-experimental design, the study involved 326 11th-grade students from a municipal high school in Kaohsiung City, Taiwan, with 189 students in the intervention group and 137 in the comparison group. Conducted in 2023, the intervention group participated in baseline and follow-up assessments and attended four 50 min media literacy sessions, while the comparison group completed only baseline and follow-up assessments with standard instruction. The results indicated that the media literacy intervention had positive effects on adolescents’ conceptual, attitudinal, and critical media literacy, as well as their persuasion resistance efficacy in relation to digital marketing of weight-control products. However, no significant effect was observed on purchase intention. In conclusion, media literacy interventions can effectively enhance adolescents’ media literacy and their ability to resist persuasion.